Team incentives under moral and altruistic preferences: Wich team to choose? - Roberto Sarkisian (Games, 2017)
This paper studies incentives provision when agents are characterized either by homo moralis preferences, i.e., their utility is represented by a convex combination of selfish preferences and Kantian morality, or by altruism. In a moral hazard in a team setting with two agents whose efforts affect output stochastically, I demonstrate that the power of extrinsic incentives decreases with the degrees of morality and altruism displayed by the agents, thus leading to increased profits for the principal. I also show that a team of moral agents will only be preferred if the production technology exhibits decreasing returns to efforts; the probability of a high realization of output conditional on both agents exerting effort is sufficiently high; and either the outside option for the agents is zero or the degree of morality is sufficiently low.
Keywords: 330; moral hazard in teams; optimal contracts; homo moralis preferences; altruism